THE MEANING OF THE ENGLISH VARIETY SPOKEN BY THE BALINESE VENDORS IN KUTA BEACH, BALI - Tri Setianingsih (Universitas Pendidikan Mandalika, 2015)
This study is concerned with the meaning of the English variety spoken by the Balinese vendors in Kuta beach, Bali which is located south of Denpasar City and become a tourism icon. As a part of tourism industry, Kuta beach is often visited by tourists from all over the world. There is a variety phenomenon in speaking English that may influence misinterpretation even though misunderstanding in face to face communication among the vendors and the tourists. This study aims to describe how is the semantic meaning which refers to the meaning in the dictionary and pragmatic meanings of the English variety of the Balinese vendors in Kuta beach, Bali. The result of this study is expected to be able to give new information to the readers about the meaning of the English variety spoken by the vendors in Kuta beach, Bali as a part of Sociolinguistics study. As descriptive study, the data findings in this study are described in form of words, phrases, and sentences. The data were collected by using two methods, participant observation and interview. Participant observation was mainly used to get the significant data from the subjects of the study. Audio and note taking techniques were used to collect the data during the participant observation. The result of the present study shows the meaning and characteristic English of Balinese vendors in Kuta beach, Bali is different from the meaning of the English used by the tourists (native speaker). Some English phrases which they use sound uncommon and sometimes they are ambiguous when they are used within a sentence.